Comparação de dois métodos de aferição do desgaste dentinário na zona de risco de molares inferiores - Corrêa, Fernanda Gomez (2013)
The aim of this study was compared two measurement methods of dentin in wear risk of mandibular molars. The distal dentin thickness wall of the mesial canals, at 2 mm of ten molar furcation, was measured before and after the cervical preparation with CPDrill ® through the Cone Beam Tomography (apparent image) and through the Stereomicroscope (real image) in order to verify if the first provided trusted values, even though an examination by image. After analysis in Image Tool computer program, the results were subjected to statistical analysis of Mann-Whitney. The result of this study showed that there was no statistical difference between the values obtained (p ˃ 0.5) in Stereomicroscope and Cone Beam computed tomography. Within the methodology of this study was possible to conclude that the Cone Beam Tomography (Imaging examination) allows to evaluate the dentin wear as similar as real values.